Marine-derived arginase: A natural weapon against cancer - Noora Barzkar; Olga Babich; Hossein Hafezi; Stanislav Sukhikh (Elsevier, 2025)
In marine species, including bacteria, fungi, invertebrates, reptiles, and birds, arginase is the final enzyme in the urea cycle within the liver. This review aims to highlight the anticancer activity of these enzymes. The metalloenzyme L-arginase (also called L-arginine amidohydrolase) catalyzes the hydrolysis of L-arginine into Ornithine and urea. Up till now, L-methionine has been partially studied in some bacterial species. It is necessary to study L-arginase and L-methionine in marine microorganisms and to optimize cultivation conditions for both enzymes using the most potent isolates. Maximum activity of L-arginase occurs under optimal conditions when temperature, carbon and nitrogen sources, and L-arginine concentration are selected. The specific activity of the enzyme was 111.383 units/mg with a yield of 4.522 and a multiplicity of 5.622 % when precipitated with ammonium sulfate at 40 % saturation. Partially purified L-arginase was eluted from gel filtration with a multiplicity of 10.627 and a recovery of 7.132 %. L-arginase, derived from the submerged cultures of the heat tolerant fungus Penicillium chrysogenum, exhibited strong resistance to high temperatures at 40 ◦C and displayed a threefold increase in its attraction to L-arginine (Km 4.8 mM). The substrate specificity of the enzyme was evaluated against different substrates such as L-arginine and L-asp arginine. The enzyme showed good affinity to L-arginine with 112 U/mL. It was found to have very low specificity for d-arginine and least specificity for others. The enzyme showed higher antiproliferative activity on Jurkat cell lines, clone E6–1, compared to other tested cell lines. These changes reflect significant differences in the regulation of biochemical processes, which is obviously manifested in the possibilities of survival and development in a particular environment and can be considered a manifestation of “biochemical adaptation” to certain environmental conditions.